Selenium dan Vitamin C Sebagai Pengobatan Pencegahan Pada Keracunan Pestisida (Studi Eksperimen Pada Petani Penyemprot di Temanggung Jawa Tengah) - Suwondo, Ari (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2010)
Symptoms of organophosphate intoxication are a result of blocking the activity of blood cholinesteraseenzyme (ChEA). The ability of liver to do de toxification using pathway of O-Dealchylation onorganophosphate and cholinesterase bound and helped out by Glutathione peroxides enzyme (GPX) hasimportant role in returning the level of ChEA to the normal level. GPX is dependent on the presence ofselenium. The objective of this study is to obtain more understandable benefit of adding selenium andvitamin C towards the ChEA, GPX and hemoglobin level of farmers worked as pesticide sprayers.This is an experimental study using Pretest-posttest Control Group Design. Ninety nine respondents inPasuruan village, sub district of Bulu, Temanggung who fulfilled inclusion and exclusion criteria wereselected as study samples. Samples were divided into 3 groups of 33 people. First group received onlySelenium, second group received Selenium and Vitamin C and third group is a control group (nosupplementation given). Blood samples of all study samples were taken to identify the level of ChEA, GPXand hemoglobin before and after experimentLevel of ChEA in the first group compared with the third group was significantly different (p=0.05). Similarfinding was also found for the level of ChEA in second group compared with third group (p= 0.014).Supplementation of Selenium 200 Î¼g for 7 days among pesticides sprayers farmers increase 1.85% level of ChEA and 2.66% level of hemoglobin.Keywords: Selenium, vit C, level of GPX, ChEA and Hemoglobin.permalink : http://ejournal.undip.ac.id/index.php/mkmi/article/view/2792Â